IMPROVING STUDENTS’ VOCABULARY ABOUT ADEJCTIVE TO DESCRIBE PEOPLE BY USING PICTURE - Heny, Hercuana; Marbun, Rismaya; Rosnija, Eny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract : The purpose of the study is to to know how well picture improves the students’ vocabulary about adjective to describe people for the tenth grade students of SMA Negeri 1 Sungai Melayu Rayak in academic year 2013/2014. The observation check list and field notes were used to take notes about teaching learning activities which related to the used of picture to teach vocabulary. Based on the research findings that had been conducted by the researcher, it could be seen that there were some improvement on students’ vocabulary achievement by using picture. On the first test the means score was 52.6 and the mean score of the second test was 77. These mean scores indicated that there were some improvements in the students. The processes done by the teacher in the classroom worked. Therefore the tenth Grade Students of SMA Negeri 1 Sungai Melayu Rayak in Academic Year 2013/2014 could improve their vocabulary score achievement by using picture. Action hypothesis showed that picture can improve the students’ vocabulary achievement. Keywords : Teaching, Vocabulary, Picture Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui seberapa baik gambar meningkatkan kosakata siswa tentang sifat untuk menggambarkan orang untuk siswa kelas X SMA Negeri 1 Sungai Melayu Rayak di tahun akademik 2013/2014. Dalam penelitian tersebut. Pengamatan check list dan catatan lapangan yang digunakan untuk mengambil catatan tentang kegiatan belajar mengajar yang berkaitan dengan yang digunakan gambar untuk mengajar kosa kata. Berdasarkan temuan penelitian yang telah dilakukan oleh peneliti, dapat dilihat bahwa ada beberapa perbaikan pada prestasi kosakata siswa dengan menggunakan gambar. Pada tes pertama skor sarana adalah 52,6 dan nilai rata-rata dari tes kedua adalah 77. ini berarti skor menunjukkan bahwa ada beberapa perbaikan dalam siswa. Proses dilakukan oleh guru di kelas bekerja. Oleh karena itu Siswa Kelas X SMA Negeri 1 Sungai Melayu Rayak di Tahun Akademik 2013/2014 bisa meningkatkan nilai kosakata prestasi mereka dengan menggunakan gambar. Aksi hipotesis menunjukkan bahwa gambar dapat meningkatkan prestasi kosakata siswa. Keywords : Mengajar, Kosa Kata, Gambar